Hydrogeological vulnerability in Jacó coastal aquifers, Central Pacific, Costa Rica - Gómez-Cruz, Alicia (2019)
In the last two decades, the Central Pacific of Costa Rica experienced a strong growth in urban and tourism development. If not regulated, this development can result in a pressure to groundwater resources and, therefore, a threat in terms of quality and quantity. In this study, a hydrogeological vulnerability map of Jacó aquifers was performed, by the GOD method. Geological profiles were elaborated, and field verification was performed. It is confirmed that, in the study area, two aquifers are found: a) a detritic, porous, unconfined coastal aquifer, settled in the Jacó alluvial plain and, b) an aquifer in the basaltic fractured rocks of the Nicoya Complex, unconfined in the mountainous zone and underlying the detritic formation in the central area, where the groundwater is integrated to that of the detrital aquifer. The zone of the alluvial aquifer resulted in a medium vulnerability index, whereas the mountainous areas in a low vulnerability. Management recommendations were proposed.